SPE EUROPEC/EAGE Annual Conference and Exhibition 2011
DOI: 10.2118/143030-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three-Phase Relative Permeability Models for WAG Injection Using Water-Wet and Mixed-Wet Core Flood Experiments

Abstract: Three-phase flow occurs during many important processes in oil reservoirs including tertiary gas and water-alternating-gas (WAG) injection. Accurate estimation of three-phase relative permeability (kr) is required to describe and predict the behaviour of these multi-phase flow conditions. The current approach in the oil industry for simulation of WAG experiments is to use two-phase relative permeability data to generate three-phase kr values by using correlations (e.g. Stone1, Baker, etc) available in commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…It was observed that, in general, the irreversibility in relative permeabilities was more profound for the water‐wet core than the intermediate‐wet core. Shahverdi et al [, ] conducted several WAG experiments under water‐wet and mixed‐wet wettability conditions. Each experiment included three cycles of water injection and gas injection.…”
Section: Effects Of Saturation Historymentioning
confidence: 99%
“…It was observed that, in general, the irreversibility in relative permeabilities was more profound for the water‐wet core than the intermediate‐wet core. Shahverdi et al [, ] conducted several WAG experiments under water‐wet and mixed‐wet wettability conditions. Each experiment included three cycles of water injection and gas injection.…”
Section: Effects Of Saturation Historymentioning
confidence: 99%
“…The laboratory work of Akin and Demiral 1997 concluded that for 3-phase imbibition relative permeability the gas relative permeability increased with increasing flow rate. Irreversible hysteresis of oil in a water-wet system was found by Shahverdi et al, 2011, which they note contradicts other research and models. A standard approach is to apply a normalized Stone method.…”
Section: Hysteresis In 3-phase Relative Permeabilitymentioning
confidence: 80%
“…Larsen and Skauge, 1999 describe a method in which they determined the Lands coefficient experimentally by a gas flood followed by a water flood. Shahverdi et al, 2011 suggest that the Land equation approach is inadequate for non-water-wet applications.…”
Section: Recovery Mechanism Theorymentioning
confidence: 99%
“…It implies that the saturation-averaged interpolation method is a common choice in more-recent models in place of other mathematical models, such as capillary models, statistical models, and network models. Several investigators (Fayers and Matthews 1984;Delshad and Pope 1989;Baker 1988;Oak 1990Oak , 1991Hustad and Holt 1992;Skjaeveland and Kleppe 1992;Balbinski et al 1999;Pejic and Maini 2003;Spiteri et al 2008;Ahmadloo et al 2009) have identified various limitations of classical three-phase relative permeability models such as Stone I (Stone 1970) and Stone II (Stone 1973), especially for nonwater-wet rocks and/or at low oil saturation. Although the majority of three-phase relative permeability models found in Table 1 are applicable only to water-wet conditions, many oil reservoirs are not strongly water-wet and their wettability may be altered in various ways (Treiber and Owens 1972;Morrow 1990).…”
Section: Three-phase Relative Permeability Modelsmentioning
confidence: 99%